AWARENESS, TREATMENT AND CONTROL OF TYPE II DIABETES IN MAURITIUS: A QUALITATIVE STUDY - Nishaat, Beebeejaun Zareen; Raveena, Hemrage (PEOPLE: International Journal of Social Sciences, 2018)
The study focuses on examining the prevalence, treatment preferences and knowledge about Type II diabetes in Mauritius. Despite the fact that the rate of Type II diabetes has been stabilized for the past 30 years, Mauritius is still one among the countries which has a very high rate of diabetes. Poor eating habits and adopting an unhealthy lifestyle are two of the major reasons for this increased rate of Type II diabetes. The objectives of this study is to find out the level of awareness of Type II diabetes in Mauritius, to understand the variations of treatment preferences among social groups and to find out whether diabetes campaigns are effective in the prevention of this illness. In order to obtain data from Type II diabetes patients on their treatment preferences and their level of awareness, in-depth face to face interviews were conducted with 15 participants in a public hospital, a local health Centre and a private clinic of the Island. Findings show that nutritional knowledge concerning food and a healthy lifestyle was low among the participants, which caused them to suffer from Type II diabetes. In addition to that, some of the informants claimed that they are not able to consume a healthy diet on a daily basis due to the lack of money. However, with strategies implemented by the health care systems such as educational talks on Type II diabetes, campaigns and distribution of pamphlets and brochures, diabetic people are able to control their illnesses by adopting a healthy lifestyle.